Control of erucic acid biosynthesis in Camelina (Camelina sativa) by antisense technology: Control of erucic biosynthesis in Camelina - Bashiri, Hoda; Kahrizi, Danial; Salmanian, Ali Hatef; Rahnama, Hassan; Azadi, Pejman (Cellular and Molecular Biology, 2023)
Oil seeds now make up the world's second-largest food source after cereals. In recent years, the medicinal- oil plant Camelina sativa has attracted much attention for its high levels of unsaturated fatty acids and low levels of saturated fatty acids as well as its resistance to abiotic stresses. Improvement of oil quality is considered an important trait in this plant. Erucic acid is one of the fatty acids affecting the quality of camelina oil. Altering the fatty acid composition in camelina oil through genetic manipulation requires the identification, isolation, and cloning of genes involved in fatty acid biosynthesis. The Fatty Acid Elangase 1 (FAE1) gene encoded the enzyme β-ketoacyl COA synthase (KCS), which is a key factor in the biosynthesis of erucic acid. In this study, isolation and cloning of the FAE1 from the Camelina sativa were performed to prepare an antisense structure. The fragments were isolated from the DNA source of the genomic Soheil cultivar with an erucic acid content of about 3% (in matured seeds) using PCR. After cloning FAE1 into the Bluescriprt II SK+ vector and sequencing, these fragments were used for the preparation of antisense structure in the pBI121 plant expression vector. The approved structure was transferred to the camelina plant via the Agrobacterium-mediated method. Also, the conditions of tissue culture and gene transfer were optimized. Moreover, the erucic acid content of the immature seeds of T0 transgenic plants was analyzed with gas chromatography (GC). Results showed significant changes in erucic acid levels of two control plants (0.88%), while two lines of the RFAE1 transgenic plants showed a decrease of approximately 0% in erucic acid level. It can be concluded that the antisense structure can be effective in reducing erucic acid.